2017
DOI: 10.1016/j.concog.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

By-passing strategic retrieval: Experimentally induced spontaneous episodic memories in 35- and 46-month-old children

Abstract: Most parents have experienced their preschool child having spontaneous episodic memories, that is, verbally reported memories of past events that come to the child almost out of the blue. Until recently such memories had only been observed outside the lab. By means of a new paradigm we report experimentally induced spontaneous memories of a unique event experienced one week earlier in 35- and 46-month-old children (N=110). At the first visit, half of the children experienced a Teddy event and the other half ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
114
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(134 citation statements)
references
References 37 publications
17
114
3
Order By: Relevance
“…While the recent study by Krøjgaard et al (2017) showed that spontaneous recall can indeed be induced in young children, we do not know exactly what type of cues made the children spontaneously remember the target event. The experimental set-up used in Krøjgaard et al (2017) allows us to investigate this more thoroughly. In the present study, we therefore focus on the possible impact of contextual cues (i.e., manipulating whether or not the children return to the same room).…”
Section: Spontaneous Retrieval In Childrenmentioning
confidence: 74%
See 3 more Smart Citations
“…While the recent study by Krøjgaard et al (2017) showed that spontaneous recall can indeed be induced in young children, we do not know exactly what type of cues made the children spontaneously remember the target event. The experimental set-up used in Krøjgaard et al (2017) allows us to investigate this more thoroughly. In the present study, we therefore focus on the possible impact of contextual cues (i.e., manipulating whether or not the children return to the same room).…”
Section: Spontaneous Retrieval In Childrenmentioning
confidence: 74%
“…Recently, a novel experimental procedure provided evidence that spontaneous memories can be induced in young children under controlled conditions (Krøjgaard, Kingo, Dahl, & Berntsen, 2014) -even for unique events (Krøjgaard, Kingo, Jensen, & Berntsen, 2017). The development of this novel experimental paradigm provides a unique opportunity for investigating spontaneous memories in children more closely.…”
Section: Spontaneous Retrieval In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, findings from Caza and Atance and McCormack et al replicate and extend the results of studies on spontaneous episodic memories in young children, which also show small or no age effects and suggest that both past and future spontaneous thoughts may be a precursor of more deliberate forms of mental time travel in everyday life (cf. Krøjgaard, Kingo, Jensen, & Berntsen, 2017). It is obvious that future research should investigate in more detail similarities and differences between the developmental trajectories of deliberate and spontaneous future thinking while, at the same time, comparing it to the deliberate and spontaneous recall of past events.…”
Section: Development Across the Life Spanmentioning
confidence: 99%